HERMETISMO Y DISTANCIA GEOGRAFICA EN SOCIEDADES DE CAMPONOTUS MOROSUS SMITH, 1858 (HYMENOPTERA: FORMICIDAE) - Ipinza-Regla, Joaquín H.; Morales, M. A.; Sepulveda, S. (Acta Entomológica Chilena, 2022)
In societies of Camponotus morosus Smith, 1858, the influence of geographic distance over the interactions of individuáis of the same species was studied in artificial nests mantained in a laboratory setting. The nests were collected in the región of Los Andes (Central Chile). First a nest, including ants named as "residents", was designated as the "zero distance nest". Then, ants named as "intruders" were collected from nests located at: 10 m, 100 m, 200 m, 2,000 m, 5,000 m and 10,000 m., from zero distance nest. The latency time of presentation of the following behavioral units were measured: antennal exploration, mandibular opening, snatching, dorsal or ventral abdominal flexión, abrupt retreat movements and, as a final event, kiUing of the intruder were measured. Significant differences were observed between nests located at 10 m, 100 m, 200 m compared to nests at 2,000 m, 5,000 m and 10,000 m.